Measuring social vulnerability in communities and its association with leprosy burden through spatial intelligence in central West Brazil to guide strategic actions - José Francisco Martoreli Júnior; Antônio Carlos Vieira Ramos; Josilene Dália Alves; Thaís Zamboni Berra; Yan Mathias Alves; Reginaldo Bazon Vaz Tavares; Letícia Perticarrara Ferezin; Titilade Kehinde Ayandeyi Teibo; Ricardo Alexandre Arcêncio (Archives of Public Health)
Abstract Background It is known that leprosy is a socially determined disease, but most studies using spatial analysis have not considered the vulnerabilities present in these territories. Objectives To measure the association between social vulnerability and the burden of leprosy in the urban space of Cuiabá. Methods Ecological study, carried out in Cuiabá, Brazil. Diagnosed cases of leprosy were surveyed through the Notifiable Diseases Information System, from 2008 to 2018. The spatial scan statistics technique of leprosy cases per each Human Development Unit was applied. Social vulnerability was measured based on the Municipal Human Development Index (MHDI), education level and average per capita income. For the spatial correlation between vulnerability and leprosy, Global and local bivariate Moran’s index was used. Results 8389 cases of leprosy were georeferenced, the majority being male (58%), 30% of cases were not evaluated for degree of physical disability. One of the spatial scan clusters had a relative risk (RR) of 6.93 (95% CI 6.49–7.4), and another had 1360 cases with RR 1.71 (95% CI 1.62–1.82). The bivariate global autocorrelation of Moran’s index for MHDI was 0.579, observing 1 High-High in the East region and 1 in South, for education the index was 0.429, 2 High-High in the East and 1 in the South, and 0.145 for average per capita income, 1 High-High in the East. Conclusion There was a spatial association between leprosy cases and territories with low MHDI, having a percentage of the population without schooling and/or with low income. The study advances knowledge by presenting characteristics of territories most affected by leprosy, verifying the spatial correlation of the disease with the recurrent socioeconomic characteristics in these territories.